2012
DOI: 10.1109/jphot.2012.2191276
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the LED Materials and Architectures for Energy-Saving Solid-State Lighting Toward “Lighting Revolution”

Abstract: In this paper, we review the recent developments (in years 2010-2011) of energysaving solid-state lighting. The industry of white light-emitting diodes (LEDs) has made significant progress, and today, white LED market is increasing (mostly with increasing LED screen and LED TV sales). The so-called Blighting revolution[ has not yet really happened on a wide scale because of the lighting efficiency at a given ownership cost. Nevertheless, the rapid development of the white LEDs is expected to soon trigger and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
88
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(88 citation statements)
references
References 62 publications
0
88
0
Order By: Relevance
“…Accordingly, the electric field at "A" site in Device II can be given by (2) [refer to Fig. 6(c)], while it can be expressed in (3) for Device III if the diffused from the doped part in the quantum barrier is negligible compared to as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, the electric field at "A" site in Device II can be given by (2) [refer to Fig. 6(c)], while it can be expressed in (3) for Device III if the diffused from the doped part in the quantum barrier is negligible compared to as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3(a)]. Moreover, the more increased in Device III compared to Device II is attributed to the reduced electric field at "A" site compared to Device II, as a reduced field at "A" site that is caused by the absence of ionized Si dopants [refer to (2) and (3)] tilts the conduction band more (Fig. 6(e), meV for Device II and 50 meV for Device III) and pushes the electron wave function towards "B" site more [ Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…InGaN/GaN multiple quantum well (MQW) lightemitting diodes (LEDs) have made significant progress in the past three decades. [1][2][3] The device performance is, however, still limited by Auger recombination, 4,5 charge separation, 6-9 current crowding, [10][11][12] insufficient hole injection, 9,[13][14][15][16][17][18] and electron overflow from the MQW active region. [19][20][21][22] In order to address these issues, a staggered quantum well architecture and also InGaN/GaN MQWs with Si-step-doped quantum barriers have been proposed to screen the quantum confined Stark effect (QCSE) and increase the spatial overlap of electron-hole wave functions, [7][8][9] while an improved current spreading can be obtained either by making the p-type layer more resistive or the p-contact layer more conductive.…”
mentioning
confidence: 99%
“…The developed multi-colored LED system can generate more than 70 colors and overcome the weakness of the conventional single LED which emits only one color. Many studies have been reported in measuring the information of the light source [17][18][19]. Most of them were to identify the color temperature, luminance, and color rendering index using a spectrometer.…”
Section: Resultsmentioning
confidence: 99%